Effect of Dietary Inclusion of Lemon Balm (Melissa Officinalis L.) Extract on Performance, Gut Microflora, Blood Parameters, Immunity and Carcass Traits of Broilers - Monireh Poorghasemi; Alireza Seidavi; Mehrdad Mohammadi; João Simões; Vito Laudadio; Vincenzo Tufarelli (The Journal of Poultry Science, 2017)
The aim of the present study was to evaluate the effects of lemon balm (LB; Melissa officinalis L.) extract as additive on performance, health status and carcass traits of broilers during a 42-days production cycle. One hundred mixed chicks of Ross 308 strain were assigned for five dietary treatments with four replicates per group and five birds per replicate as follows: control diet, 0.5LB, 1.0LB, 1.5LB and 2.0LB with 0.0, 0.5, 1.0, 1.5 or 2.0 mL of LB extract per liter of drinking water, respectively. In overall, at 42nd day, low feed, energy and protein efficiency (P<0.05) were observed in 1.0LB group than in control diet. However, during the 3rd and 5-6th weeks, feed, energy and protein intakes were improved (P<0.05), without any efficiency enhancement (P>0.05) mainly in group on 1.0LB diet. During the 5th week of rearing, daily weight gain was higher (P<0.05) in groups 0.5LB, 1.0LB and 2.0LB compared to control diet. At the end of feeding period, cecal enterococcus bacteria colony count was higher (P<0.05) and left cecum diameter was lower (P<0.05) in 1.0LB group. Hematological parameters and viscera and carcass traits remained unaffected (P>0.05) by dietary treatments. In conclusion, the supplementation with LB as natural feed additive resulted in a potential positive effect on broilers performance mainly during the grower and finisher periods.